2020
DOI: 10.11604/pamj.2020.36.285.18858
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of problematic smart phone use among pre-varsity young people in Ibadan, Nigeria

Abstract: Introduction smart phone possession and use among young people is on the increase in Africa and phone addiction has been shown to be similar to substance use dependence. However, there is barely any literature focused on the effect of smart phone use on young people in Nigeria. This study looked at the prevalence of problematic smart phone use and associated factors among pre-varsity young people in Ibadan. Methods problematic smart phone use was assessed using the 27-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
1
17
0
2
Order By: Relevance
“…In relation to the type of internet access, a signi cant difference was found between those who do access the internet by paying for data packages (p=0.000). Similar results were found by Balogun and Olatunde [46], who studied the problems of smartphone use among the young population; they found that the data used for the phones are mainly nanced by the parents. These phones are used to surf the internet, make calls, and send text messages.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In relation to the type of internet access, a signi cant difference was found between those who do access the internet by paying for data packages (p=0.000). Similar results were found by Balogun and Olatunde [46], who studied the problems of smartphone use among the young population; they found that the data used for the phones are mainly nanced by the parents. These phones are used to surf the internet, make calls, and send text messages.…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, Balogun and Olatunde [46] studied the problems of smartphone use in a population of 1230 young people and young adults, with the distribution of socioeconomic classes in a (27.8%) Class I, (58.2%) Class II, (12.4%) Class III and (1.6%) Class IV. Access to the phone and phone use by the respondents showed a prevalence of 96.7% with positive activation of smartphone functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although smartphone penetrations across the world, including in developing nations, are hailed because of several affordances (GSMA-GSM Association, 2008;National Bureau of Statistics, 2018;NCC, 2019), conventional media technologically tilted programs and content production practices (Sambe & Nyam, 2018) as well as mobile telecommunication convergences (Nyam & Olubodede, 2020;Nyam & Oyewole, 2020), and news aggregations (Nyam & Sambe, 2021;Nyam & Uwujiougu, 2021), there are equally some compelling issues. One of such contentions about the spread and use of smartphones is that they can harm academic performance (Balogun & Olatunde, 2020). Indeed, research investigating the role of smartphones for academic enhancement is scarce, let alone the use of smartphones' inherent mechanisms for improved user control and addiction avoidance toward enhanced academic performances.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Media technologies are already applauded, but there are social, behavioral and psychological issues such as addiction that are connected to its gratifications (Damiao & Cavaliere, 2021). Smartphone addiction is indeed already well documented (Balogun & Olatunde, 2020;Damiao & Cavaliere, 2021;Sharma et. al., 2021).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation